2017
DOI: 10.1208/s12249-017-0928-5
|View full text |Cite
|
Sign up to set email alerts
|

Soy Protein Microparticles for Enhanced Oral Ibuprofen Delivery: Preparation, Characterization, and In Vitro Release Evaluation

Abstract: The objective of this work was to evaluate soy protein isolate (SPI) and acylated soy protein (SPA) as spray-drying encapsulation carriers for oral pharmaceutical applications. SPI acylation was performed by the Schotten-Baumann reaction. SPA, with an acylation rate of 41%, displayed a decrease in solubility in acidic conditions, whereas its solubility was unaffected by basic conditions. The drug encapsulation capacities of both SPI and SPA were tested with ibuprofen (IBU) as a model poorly soluble drug. IBU-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…This suggests that soy proteins are capable of conveying the probiotics' physiological activity to the intestine with higher functionality (González-Ferrero et al, 2018). The in vitro gastrointestinal digestion of SPI and acylated soy protein for oral ibuprofen release was studied by Castro et al (2018). The findings indicated that these proteins could be employed to increase the bioavailability of poorly soluble medications to speed up absorption in the gut (Castro et al, 2018).…”
Section: Digestibility and Bioavailability Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that soy proteins are capable of conveying the probiotics' physiological activity to the intestine with higher functionality (González-Ferrero et al, 2018). The in vitro gastrointestinal digestion of SPI and acylated soy protein for oral ibuprofen release was studied by Castro et al (2018). The findings indicated that these proteins could be employed to increase the bioavailability of poorly soluble medications to speed up absorption in the gut (Castro et al, 2018).…”
Section: Digestibility and Bioavailability Considerationsmentioning
confidence: 99%
“…The in vitro gastrointestinal digestion of SPI and acylated soy protein for oral ibuprofen release was studied by Castro et al (2018). The findings indicated that these proteins could be employed to increase the bioavailability of poorly soluble medications to speed up absorption in the gut (Castro et al, 2018). For in vitro release under stomach circumstances alone and in conjunction with intestinal conditions, flaxseed oil that has been encapsulated with the combination of SPI and modified starch was tested.…”
Section: Digestibility and Bioavailability Considerationsmentioning
confidence: 99%
“…The two thermal steps concerning the mass losses, from 200 to 300 C, could be related to the breaking of the alginate backbone as well as loss of OH groups due to the dehydration. [54,55] Above 300 C, SA is known to decarboxylate releasing CO 2 and other low molecular weight gases, while soy protein degradation occurred between 250 C and 450 C. [56] The presence of HH did not lead to further decomposition steps since the thermal decomposition of its main compounds (holocellulose, cellulose, hemicellulose, and lignin) occurred roughly in the same temperature ranges. The last thermal step (470-570 C) could then be related to the dehydroxylation of Al-OH groups.…”
Section: Tga Analysismentioning
confidence: 99%
“…These microgels can be a useful tool for tissue engineering. In addition, Anaya Castro et al (2018) produced SPI and acylated soy protein microparticles by spraydrying to encapsulate and release ibuprofen (a poorly soluble drug model). These authors obtained high microencapsulation efficiencies, confirming the excellent properties of these proteins to encapsulate and be used as pH-sensitive delivery systems for the oral route (Anaya Castro et al, 2018).…”
Section: Macro-and Microscale Structuresmentioning
confidence: 99%